Novel multifunctional nanofibers based on thermoplastic polyurethane and ionic liquid: towards antibacterial, anti-electrostatic and hydrophilic nonwovens by electrospinning. (17th February 2015) - Xing, Chenyang; Guan, Jipeng; Chen, Zhouli; Zhu, Yu; Zhang, Bowu; Li, Yongjin; Li, Jingye
Abstract: Novel antibacterial, anti-electrostatic, and hydrophilic nanofibers based on a blend containing thermoplastic polyurethane (TPU) and a room-temperature ionic liquid (IL), 1-butyl-3-methylimidazolium hexafluorophosphate [BMIM][PF6 ], were fabricated by electrospinning. We investigated the effect of the IL on the morphology and the physical properties of the TPU nanofibers. Nanofibers with a 'bead-on-string' morphology were obtained by electrospinning from a neat TPU solution. The incorporation of the IL, at levels as low as 1 wt%, largely suppressed the formation of beads during electrospinning, and homogeneous nanofibers were obtained. The as-spun TPU/IL composite nanofibers showed significant activity against both Escherichia coli ( E coli) and Staphylococcus aureus ( S. aureus ), with antibacterial activities of more than four and three, respectively. This means that the antibacterial efficiencies of TPU/IL composite nanofibers toward E coli and S. aureus are 99.99% and 99.9%, respectively. Moreover, nonwoven fabrics derived from the electrospun TPU/IL composite nanofibers exhibit better stretchability, elasticity, and higher electrical conductivity compared to those made using neat TPU without an IL. Additionally, the incorporation of the IL leads to a hydrophilic surface for the TPU/IL composite nanofibers compared to hydrophobic neat TPU nanofibers. These multifunctional nanofibers with excellent antibacterial, anti-electrostatic, and mechanical properties and improved hydrophilicity are promising candidates for biomedical and wastewater treatment applications.